2017
DOI: 10.1021/acs.inorgchem.6b02694
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Trends in Solid Alkali Pertechnetates

Abstract: Insight into the solid-state chemistry of pure technetium-99 (Tc) oxides is required in the development of a robust immobilization and disposal system for nuclear waste stemming from the radiopharmaceutical industry, from the production of nuclear weapons, and from spent nuclear fuel. However, because of its radiotoxicity and the subsequent requirement of special facilities and handling procedures for research, only a few studies have been completed, many of which are over 20 years old. In this study, we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 70 publications
6
35
1
Order By: Relevance
“…A similar phenomenon has previously been observed in the structure of anilinium pertechnetate (Maruk et al, 2010). The greatest distortion of the TcO 4 À anion from an ideal tetrahedral configuration reported by Weaver et al 2017is confirmed by our analysis of the O-Tc-O angles in the NaTcO 4 structure, but the difference is not as high as in the model from the neutron diffraction experiment (Weaver et al, 2017). The maximum deviation values are 3.12 at 100 K and 3.08 at 296 K for the sodium salt and are larger in comparison with the potassium and rubidium salts, because the sodium cation has the smallest ionic radius compared to K + and Rb + and hence has the highest polarizing ability.…”
Section: Tablesupporting
confidence: 89%
See 3 more Smart Citations
“…A similar phenomenon has previously been observed in the structure of anilinium pertechnetate (Maruk et al, 2010). The greatest distortion of the TcO 4 À anion from an ideal tetrahedral configuration reported by Weaver et al 2017is confirmed by our analysis of the O-Tc-O angles in the NaTcO 4 structure, but the difference is not as high as in the model from the neutron diffraction experiment (Weaver et al, 2017). The maximum deviation values are 3.12 at 100 K and 3.08 at 296 K for the sodium salt and are larger in comparison with the potassium and rubidium salts, because the sodium cation has the smallest ionic radius compared to K + and Rb + and hence has the highest polarizing ability.…”
Section: Tablesupporting
confidence: 89%
“…The structure of anhydrous NaTcO 4 , determined here on the basis of X-ray diffraction data of a single crystal recorded both at room and low temperature, belongs to the CaWO 4 structural type (space group type I4 1 /a). The obtained bond lengths and angles are similar to those obtained from previous X-ray powder (Keller & Kanellakopulos, 1963;Schwochau, 1962) and neutron powder diffraction studies (Weaver et al, 2017) Lattice parameters determined here with the precision of 0.0002-0.0005 Å at 296 K (Table 1) are close to those of a = 5.342 (3) Å , c = 11.874 (6) Å given by Weaver et al (2017). The lattice parameters at 100 K are a = 5.2945 (2) Å , c = 11.7470 (5) Å (single crystal measurement).…”
Section: Structural Commentarysupporting
confidence: 86%
See 2 more Smart Citations
“…Within the last few decades there has been a significant increase in research efforts to learn how best to store and dispose of Tc for these purposes [8][9][10][11][12][13][14][15][16]. Coupled with these efforts has been a push for advanced analyses of Tc bearing materials using state-of-the-art equipment [12,[17][18][19][20][21][22][23]. X-ray absorption fine structure (XAFS) has been utilized to investigate the near-field structures of Tc in both crystals and soft matter.…”
Section: Introductionmentioning
confidence: 99%